Bibliotherapy features in children’s literature: a systematic literature review/ Rafidah Abdul Aziz ... [et al.] - Abdul Aziz, Rafidah; Wan Mohd Saman, Wan Satirah; Shaifuddin, Norshila; Mohd. Radzi, Salleh (Faculty of Information Management, 2025)
Children's literature is a powerful tool in bibliotherapy, helping children navigate social and emotional challenges by connecting them with relatable characters and situations. This therapeutic method embraces diverse perspectives and relevant issues, encouraging the development of new values. The current study reviews literature on bibliotherapy features in children’s literature with the purposes of ascertaining the attributes and components of children's literature that may potentially facilitate emotional metamorphosis and bolster personal development. The review selected 33 English-language publications in the field of bibliotherapy and children’s literature from peer-reviewed journals indexed in the Web of Science, and Scopus. The major findings demonstrate that the effective bibliotherapy focus on key elements such as well-crafted characters, compelling plots, universal themes, and empathy, supported by high-quality writing and illustrations. Additionally, the process is highly personalized, taking into account readability and the child’s developmental stage. Overall, bibliotherapy provides a valuable approach for nurturing emotional and psychological growth, offering a safe space for children to explore and reflect through literature. Selecting appropriate literary materials is essential to maximizing its therapeutic impact. The results form the basis for several recommendations for future research for the further examination of bibliotherapy features for children literature.